The craft of knowledge: sounds, objects and enigmas in the memory of children in exile (Clepsidra - Interdisciplinary Journal of Memory Studies, 2023)
The following paper is part of my doctoral research that explores the childhood memories of those who experienced exile during the last dictatorships in Uruguay and Argentina. From there, I seek to investigate the link between the forms of knowledge, politics and affects that shaped the subjective experiences of the children of that time. In the following text, I intend to focus on the everyday crafts that children of that time made in order to assemble different materialities of knowledge, available in their environment, about their family history. In these searches, the modes of agency and the active gaze of the children of the time are reconstructed in the elaboration of a story about the past that drove them into exile.
Keywords: Childhood, Memory, Exile, Objects, Sounds, Children's Agency